The Ethical Perils of Personal, Communal Relations: A Language Perspective. (December 2019) - Kouchaki, Maryam; Gino, Francesca; Feldman, Yuval
Most companies use codes of conduct, ethics training, and regular communication to ensure that employees know about rules to follow to avoid misconduct. In the present research, we focused on the type of language used in codes of conduct and showed that impersonal language (e.g., "employees" or "members") and personal, communal language (e.g., "we") lead to different behaviors because they change how people perceive the group or organization of which they are a part. Using multiple methods, including lab- and field-based experiments (total N = 1, 443), and a large data set of S&P 500 firms (i.e., publicly traded, large U.S. companies that are part of the S&P 500 stock market index), we robustly demonstrated that personal, communal language (compared with impersonal language) influences perceptions of a group's warmth, which, in turn, increases levels of dishonesty among its members.